Kajian Etnobotani Tumbuhan Penghasil Karbohidrat: Pengetahuan Lokal dan Potensi Diversifikasi Pangan di Pandansari Lor, Malang - Aliyatul Karimah; Arni Tri Habsari; Arum Maqfiroh; Muhammad Dul Firdaus; Fahrul Ghani Muhaimin; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Local carbohydrate-producing food plants play an important role in supporting food security and preserving local knowledge. This study aims to identify the diversity and utilization of carbohydrate-producing plants, and analyze quantitative ethnobotanical indices based on local knowledge in Pandansari Lor Village, Malang Regency. The study used an exploratory sequential mixed methods design. Data were obtained through observation, interviews, documentation, and surveys of 94 respondents. The results showed that there were 17 species of carbohydrate-producing plants utilized, dominated by herbaceous, shrubby, and tree habitus. The ICF value of 0.98 indicated a very high level of agreement among respondents. Species with the highest frequency of mention included Manihot esculenta, Zea mays, Ipomoea batatas, Oryza sativa, Musa paradisiaca, and Solanum tuberosum which also had the highest RFC value of 1. The Euphorbiaceae family had the highest FUV value of 3.85, while the most widely utilized plant part was the tuber (52.75%). The use of carbohydrate-producing plants as staple foods is still focused on a few key species, with a high level of knowledge diversification. Therefore, efforts to diversify and preserve local food plants are needed to support community food security.